Electrochemical and spectroscopic properties of electrospun PAN-based fibrous polymer electrolytes - Choi, SW; Kim, JR; Jo, SM; Lee, WS; Kim, YR (ELECTROCHEMICAL SOC INC, 2005)
Microporous fibrous polymer electrolytes were prepared by immersing electrospun poly(acrylonitrile) (PAN)-based fibrous membranes into lithium salt-based electrolytes. They showed high ionic conductivities of up to 1.0 x 10(-3) S/cm at 20 degrees C, and sufficient electrochemical stabilities of up to 4.5 V. Their ion conduction depended on the physicochemical properties of the lithium salt-based electrolytes trapped in pores, as well as on the interactions among the Li+ ion, the carbonate, and the PAN. From the Fourier transform-Raman data, lithium ion transport was mainly achieved by the lithium salt-based electrolytes in pores via the interaction between the Li+ ion and the C=O group of carbonate molecules, and was also affected by the PAN through the interaction between the Li+ ion and the C N groups of PAN. Their electrochemical stabilities were enhanced by the swelling of the electrospun PAN nanofibers because of the dipolar interaction between the C; N groups of PAN and the C=O groups of carbonate in the lithium salt-based electrolytes. Prototype cells using electrospun PAN-based fibrous polymer electrolytes thus showed different cyclic performances, according to the composition of the lithium salt-based electrolytes. The prototype cell with 1 M LiPF6-ethylene carbonate/ dimethyl carbonate (1/1) showed the highest discharge capacity and the most stable cyclic performance among them. (c) 2005 The Electrochemical Society.
Keywords: POLYACRYLONITRILE-BASED ELECTROLYTES; BINARY SOLVENT SYSTEMS; LITHIUM-ION BATTERIES; ETHYLENE CARBONATE; GEL ELECTROLYTES; TRANSPORT-PROPERTIES; PHASE-DIAGRAMS; CONDUCTIVITY; RAMAN; PLASTICIZER